2013
DOI: 10.1007/s00018-013-1504-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in myocardial ischemia: identifying new targets and tools for treating heart disease. New frontiers for miR-medicine

Abstract: (miRNAs as disease biomarkers) and miR-drugs (miRNAs as therapeutic targets) for cardiac ischemia and heart failure. Finally, we evaluate the use of miRNAs in the emerging field of regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 161 publications
0
30
0
Order By: Relevance
“…161 A general classification could distinguish the miRNAs that typically are elevated in congestive heart failure, such as miR-21, miR-29b, miR-34, miR-122, miR-129, miR-142-3p, miR-199, miR-210, miR-211, miR-212, miR-379, miR-423-5p, and miR-503, and those with downregulated levels, such as miR-30, miR-107, miR-125b, miR-126, miR-139, miR-142-5p, miR-182, miR-497, and miR-526. 162,163 More specifically, it has been indicated that miRNA-1 expression may be inversely correlated with cardiac hypertrophy, atrial dilatation, and cardiac hypertrophy. 125,164 Furthermore, recent data show that miR-126 and miR-508-5p could be used for diagnostic and therapeutic purposes because of the fact that their levels in endothelial progenitor cells correlate with the long-term prognosis of ischemic cardiomyopathy and congestive heart failure.…”
Section: Mirnas and Heart Failurementioning
confidence: 98%
“…161 A general classification could distinguish the miRNAs that typically are elevated in congestive heart failure, such as miR-21, miR-29b, miR-34, miR-122, miR-129, miR-142-3p, miR-199, miR-210, miR-211, miR-212, miR-379, miR-423-5p, and miR-503, and those with downregulated levels, such as miR-30, miR-107, miR-125b, miR-126, miR-139, miR-142-5p, miR-182, miR-497, and miR-526. 162,163 More specifically, it has been indicated that miRNA-1 expression may be inversely correlated with cardiac hypertrophy, atrial dilatation, and cardiac hypertrophy. 125,164 Furthermore, recent data show that miR-126 and miR-508-5p could be used for diagnostic and therapeutic purposes because of the fact that their levels in endothelial progenitor cells correlate with the long-term prognosis of ischemic cardiomyopathy and congestive heart failure.…”
Section: Mirnas and Heart Failurementioning
confidence: 98%
“…Selective coronary angiography and PCI were performed at our catheterization laboratory via the radial or femoral artery by experienced cardiologists who were blinded to the clinical data and CAC score; the subjects were randomised and selected from quantitative coronary angiography results; CAD was defined as lesions with stenosis diameters exceeding 75% of the diameter of one of the major epicardial coronary arteries or its branches or a ≥50% narrowing of the left main coronary artery (11). All lesions with stenosis diameters exceeding 75% of a ≥2 mm coronary artery or a more than 50% narrowing of the left main coronary artery were subjected to PCI.…”
Section: Coronary Angiography and Percutaneous Coronary Intervention mentioning
confidence: 99%
“…The manipulation of different miRNAs (e.g., miR-15 family, miR-195, miR-133, miR-17-92, miR-590, miR-199a), which are known to impact on the cell cycle, was shown to promote cardiomyocyte proliferation in various animal models [ 67 ]. The upregulation of the miR-15 family members, for instance, is associated with a definite withdrawal of cardiomyocytes from the cell cycle during neonatal development.…”
Section: Coronary Artery Disease (Cad) and Myocardial Infarction (Mi)mentioning
confidence: 99%